2018
DOI: 10.1155/2018/9156304
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bidirectional Impact Loading on Anomalously Low‐Friction Effect in Block Rock Media

Abstract: The anomalously low-friction effect is a key scientific problem in deep mining. The deep coal rock media is usually a block structure with joint fracture. When the deep block coal rock is subjected to repeated strong dynamic impact caused by long-term excavation activities, the anomalously low-friction effect will occur, resulting in dynamic disasters such as rock bursts. Taking granite block rock media as research object and using bidirectional impact loading to simulate the dynamic disturbance of rock media,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The weak structural plane and layered interface, which is easy to slide abruptly, are the most important factors leading to rockburst. li [5] deduced a new formula of normal force between blocks and a new formula of horizontal displacement of working blocks by establishing a theoretical model of ultra-low friction effect of block rock mass considering overburden pressure. The research shows that the decrease of normal force between blocks leads to the decrease of friction between blocks, and in the case of horizontal disturbance, it is easy to induce ultra-low friction rockburst.…”
Section: Introductionmentioning
confidence: 99%
“…The weak structural plane and layered interface, which is easy to slide abruptly, are the most important factors leading to rockburst. li [5] deduced a new formula of normal force between blocks and a new formula of horizontal displacement of working blocks by establishing a theoretical model of ultra-low friction effect of block rock mass considering overburden pressure. The research shows that the decrease of normal force between blocks leads to the decrease of friction between blocks, and in the case of horizontal disturbance, it is easy to induce ultra-low friction rockburst.…”
Section: Introductionmentioning
confidence: 99%
“…When an external disturbance load is applied on rock masses, friction between adjacent rock blocks in the orthogonal direction to the disturbance load may be significantly reduced or even completely disappeared, which is known as an anomalously low friction phenomenon [1,2]. e phenomenon may lead to serious geological disasters, such as the large-scope tunnel deformations [3][4][5] and sliptype rock bursts [6][7][8] in the surrounding rock masses around tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…A simple rock block model as shown in Figure 1 is taken to analyse the geological disasters induced by the anomalously low friction phenomena [2,17,18]. Kurlenya et al [19,20] studied the anomalously low friction phenomena in block media from various geomaterials and found that significant displacements of the working blocks occur at absolute values of plus actions, which are much smaller than the corresponding friction forces.…”
Section: Introductionmentioning
confidence: 99%